New channels of music distribution : a complete guide to music distribution, music business, promotions, and selling music - Brae, C. Michael (Routledge, 2018)
"With an example-driven, hands-on approach, New Channels of Music Distribution offers a practical, comprehensive study of the music industry's evolving distribution system. While paying careful attention to the variables that impact success, C. Michael Brae examines the functionality and components of music distribution, as well as the music industry as a whole. This book is a one-stop guide and resource for all musicians, performers, songwriters, and label owners in understanding all the elements and efficiency of music distribution. Through its hands-on exploration of the music business, this book provides insightful strategies for executing marketing, radio, retail campaigns, and much more."--Publisher's description